2014
DOI: 10.4103/0255-0857.129793
|View full text |Cite
|
Sign up to set email alerts
|

Study of complement activation, C3 and interleukin-6 levels in burn patients and their role as prognostic markers

Abstract: Complement activation, C3 and IL-6 levels correlated well with the severity of injury and development of infection in burn patients. These parameters can be used to predict the onset of infection, septicaemia and mortality in burn patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Up regulation of IL-6 was observed at wound sites during skin wound healing in mice (Satoand Ohshima, 2000).Additionally, Sasaki et al (2011) suggested positive association between IL-6 and burninduced immune-inflammatory response during the burn healing process. Increased levels of IL-6 within hours of thermal trauma have been reported by Modi et al (2014).In addition, Guo et al (1990) reported increased serum levels of IL-6 over a 3-week interval with peak concentrations reached during the first week after injury in a population of burn patients.…”
Section: Discussionmentioning
confidence: 83%
“…Up regulation of IL-6 was observed at wound sites during skin wound healing in mice (Satoand Ohshima, 2000).Additionally, Sasaki et al (2011) suggested positive association between IL-6 and burninduced immune-inflammatory response during the burn healing process. Increased levels of IL-6 within hours of thermal trauma have been reported by Modi et al (2014).In addition, Guo et al (1990) reported increased serum levels of IL-6 over a 3-week interval with peak concentrations reached during the first week after injury in a population of burn patients.…”
Section: Discussionmentioning
confidence: 83%
“…In murine models of cecal ligation and puncture (CLP), C3 and C4 deficient mice are more likely to experience septic shock, and the absence of C3 is associated with increased mortality in sepsis [6]. Low C3 has also been associated with mortality in infected humans in a handful of small observational studies [26][27][28]. To our knowledge, this is the first study to report an association between low C4 levels and mortality during gram-negative bloodstream infection, and further studies are needed to validate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation was revealed to occur mainly via the AP evidenced by a massive drop of the hemolytic activity in the alternative pathway (AH50) in the first hours following trauma, while the hemolytic activity of the classical pathway (CH50) remained normal or even supranormal [ 99 ]. C3 plasma levels are inversely correlated with the burn severity and could be used as a prognostic marker [ 100 ]. However, in the course of 2 weeks after burn, AH50 and CH50 increase concomitant with the presence of complement proteins (e.g., C3 and C4).…”
Section: Burnmentioning
confidence: 99%